Монгол улсын нутаг дахь дөрвөлжин үсгийн дурсгалууд - Ё.Жанчив (Acta Mongolica, 2008)
In this article the author analysed a next monuments in hPhags-pa Script found in Mongolia: 1. Sheep year’s edict of Togontemur khaan (1343) 2. Inscription of Khuitenii gol 3. Inscription of Khavtsaliin adag 4. Inscription of Taikhar chuluu 5. Inscription of Rashaan khad 6. Inscription of Yamaat ulaan 7. Seal inscriptions (26 seal inscriptions of old and new periods) 8. Monuments in books and sutras 9. Inscription on the coin 10. Mantra’s inscriptions Study of each monuments consists from a photography, a brief information, reconstruction in hPhags-pa script, transliteration, Chinese and tibetian renditions, mongolian translation and related bibliography